Pengaruh Terapi Yoga Anak dalam Meningkatkan Kecerdasan Emosional Anak Prasekolah di TK Perintis Geres - Yuspida Yulianti; Lestari, Puji (Universitas Ngudi Waluyo, 2021)
Emotional development in preschool children tends to increase. Children have not been able to manage emotions properly. The impact that occurs is that the child will develop anxious, gloomy, impulsive and even aggressive. Yoga has several components, one of which is relaxation techniques, these techniques can reduce tension and stress and meditation techniques that have benefits in increasing concentration and positive emotionality. The research design used was a Quasi Experiment with a Pre-Post Test Design approach with control. The sampling technique used simple random sampling. Data analysis used the Mann Whitneey test. The results of the Mann Whitney test. Before being given yoga therapy, the value of sin (p) = 0.117 was obtained. Value 0.117> 0.05. The results showed that there was no difference in the effect of children's yoga in increasing children's emotional intelligence in the experimental and control groups before being given yoga therapy. The results of the Mann Whitneey test analysis after yoga therapy with the SPSS program obtained the value of sin (p) = 0.000. Value 0.000 <0.05. The results of the Mann Whitneey test show that yoga therapy has an effect on increasing emotional intelligence after being given yoga therapy in the control and experimental groups. There are differences in the effect of children's yoga therapy in increasing children's emotional intelligence in the experimental and control groups. Abstrak Perkembangan emosi pada anak prasekolah cenderung mengalami peningkatan. Anak belum mampu dalam mengelola emosi dengan tepat. Dampak yang terjadi adalah anak akan berkembang menjadi mudah cemas, pemurung, impulsif bahkan agresif. Yoga memiliki beberapa komponen salah satunya adalah teknik relaksasi, teknik ini dapat menurunkan ketegangan dan stres dan teknik meditasi yang memiliki manfaat dalam meningkatkan konsentrasi serta emosional yang positif. Desain Penelitian yang digunakan adalah Kuasi Experiment dengan pendekatan Pre-Pos Test Design with control. Teknik pengambilan sampel menggunakan simpel random sampling. Analisa data menggunakan uji Mann Whitneey. Hasil uji Mann Whitney Sebelum diberikan terapi yoga diperoleh nilai sin (p)= 0.117. Nilai 0.117 > 0.05. Hasil menunjukan bahwa tidak ada perbedaan pengaruh yoga anak dalam meningkatkan kecerdasaan emosional anak pada kelompok eksperimen dan kontrol sebelum diberikan terapi yoga. Hasil analisis uji Mann Whitneey sesudah terapi yoga dengan program SPSS diperoleh nilai sin (p)= 0,000. Nilai 0.000 <0,05. Hasil uji Mann Whitneey menunjukan bahwa terapi yoga memiliki pengaruh terhadap peningkatan kecerdasan emosional sesudah diberikan terapi yoga pada kelompok kontrol dan eksperimen. Ada perbedaan pengaruh terapi yoga anak dalam meningkatkan kecerdasaan emosional anak pada kelompok eksperimen dan kontrol.